DEVELOPMENT OF THE HUMAN BLOOD CIRCULATION SYSTEM BOOKLET AS A TEACHING MATERIAL SUPPLEMENT OF NATURAL SCIENCE FOR CLASS VIII SMP / MTs - Firma Utari; Syamsurizal Syamsurizal (Universe, 2021)
ABSTRAK This research aims to produce a booklet as a valid teaching material supplement for the human circulatory system. This research is used Research and Development with using the Plomp model, which of several phase, namely the preliminary research phase, the development or prototyping phase and the assessment phase. Data analysis used qualitative and quantitative analysis. This booklet was validated by 5 validators consisting of 3 lecturers of Natural Science FMIPA UNP, and 2 teachers from SMP N 16 Padang. One to one evaluation was carried out with three students with different academic abilities. Booklet validity test results obtained an average value of 88.85% with valid criteria. The one to one evaluation results show that all the components of the booklet are interesting, use simple and understandable language and the images presented are clear. The conclusion obtained is that the booklet has valid criteria and is suitable for use as a teaching material supplement.